Serum levels of cobalt and chromium in a complex modular total hip arthroplasty system. - Harding, I; Bonomo, A; Crawford, R; Psychoyios, V; Delves, T; Murray, D; McLardy-Smith, P (2002)
There is concern that modularity in a total hip arthroplasty system increases serum cobalt and chromium ion levels. This study measures the serum cobalt and chromium levels in patients with an Oxford Universal Hip (Corin, Cirencester, United Kingdom), which has a modular sliding mechanism; patients with a similarly manufactured hip with no sliding mechanism; and a control group. Loosening was excluded clinically and radiologically. Arthroplasty patients had statistically higher levels of serum cobalt and chromium than controls, but there was no significant difference in levels between the implanted groups.